Analisis Penerapan E-Office Atandie Pada Direktorat Jenderal Kependudukan dan Pencatatan Sipil Kementerian Dalam Negeri - Arih Setyaningrum; Evi Satispi (CiDEA Journal, 2024)
As an embodiment of e-government the Directorate General of Population and Civil Registration of the Ministry of Home Affairs launched the e-Office system, this system was built to improve the quality of public services in terms of correspondence, communication between regions online or digitally, in its implementation there are various problems from the provider side Such services include long bureaucratic processes. The aim of this research is to analyze how Atandie e-Office is implemented at the Directorate General of Dukcapil, Ministry of Home Affairs. The research method used is descriptive with a qualitative approach and data collection techniques through interviews and observation. This research uses indicators of e-government implementation according to Indrajit (2005:13). The results of this research show that content development has been carried out for e-Office development since 2021-2022 and there will still be final development in 2023, competency building training that has already been carried out, The connectivity of the infrastructure provided is sufficient as seen from the large server capacity provided, but we still have to add a backup server, cyber laws, the legal regulations underlying e-Office are quite strong with Minister of Home Affairs Regulation N0.7 of 2019 concerning Online Population Administration Services, citizen interfaces Staff procurement is carried out approximately once a year in two ways, capital in terms of the budget applied for the construction and development of e-Office is sufficient.